Properties of subclasses of multivalent functions defined by a multiplier transformation - Darwish, H.E (Tamsui Oxford Journal of Mathematical Sciences)
In this paper we introduced new classes of p-valent functions defined by the multiplier transformation, and certain inclusion relations are established. Also, we prove that a well-known class of integral operators preserve these subclasses of A(p).